Letter recognition using backpropagation algorithm - Azrul Hafiz, Awang (2010)
Letter Recognition using Backpropagation Algorithm is an application to analyze the letter data and the performance of Backpropagation Neural Network in letter recognition. The objective of tbi project is to implement Backpropagation Neural Network for letter recognition task. This application will be developed using C++ Builder. Letter Recognition using Backpropagation Algorithm will make analysis and show the accuracy percentage, errors and the result of the letter training. The expected output will be compared with the actual output. Software Development Life Cycle (SDLC) methodology will be used in this project development to make sure all the development process is running smoothly.